Development of Tutorial Video Based Learning Media for Network Service Technology Practicum Materials in Vocational High Schools - Alfaisal, Haldi; Mangesa, Riana Tangkin; Sanatang, Sanatang (FKIP - Universitas Riau, 2025)
This study aimed to develop and evaluate video tutorial learning media for the Network Services Technology Practicum in Vocational High Schools using the HALDI development model. The research employed a Research and Development (R&D) approach, consisting of heuristic analysis, architectural design, instructional development, development testing, and implementation and dissemination stages. The feasibility of the developed media was assessed by an instrument expert, a media expert, and subject matter experts who are vocational high school teachers. The evaluation results showed feasibility percentages of 100% from the instrument expert, 100% from the media expert, and 96% from the subject matter experts, indicating a very feasible category. Practicality and effectiveness were tested through individual, small group, large group, and field trials. The individual trial showed 83% practicality and 85% effectiveness, while the small group trial achieved 90% practicality and 89% effectiveness. The large group trial resulted in 85% practicality and 88% effectiveness. Teacher responses indicated 94% practicality and 96% effectiveness. Field testing at SMK Negeri 6 Takalar and SMK Negeri 2 Makassar confirmed that the media is very practical and effective.